Sosialisasi Emotional Intelligence (EI) Terhadap Motivasi Belajar Siswa di Kelas VI MIN 5 Langkat - Ahmad Zaki; Muamar Al-Qodri; Wahyuni Wahyuni (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Emotional Intelligence (EI), also known as emotional intelligence, is a person's ability to recognize their own emotions, be able to control their emotions according to situations and conditions, be able to use their emotions to increase their own motivation, be able to recognize other people's emotions, and be able to interact positively with other people. . Emotional intelligence (EI) is a self-concept that a teacher, the aim is to increase motivation to learn without having to depend on the surrounding environment. This community service activity is aimed at class VI teachers at MIN 5 Langkat, which aims to improve the performance of teachers when teaching in the classroom by implementing an emotional intelligence system when teaching. With a teacher who can understand the characteristics of the students and understand the emotions of the students, it will be easy for the teacher to convey lesson material without having to force his will on the students. This will also influence students' learning motivation, when students feel that the teacher understands their feelings and needs, students will happily accept the learning provided by the teacher. It was proven that after participating in this socialization, several class VI teachers had implemented EI in the learning process and this had a big influence on increasing the learning motivation of class VI elementary school students.